Exploration of collaborative partnership models for sustainable teacher education in Indonesia - Ella Wulandari; Julianne Moss; Christine Ure (Universitas Ahmad Dahlan, 2026)
Research has shown that the link between coursework preparation and field experience is strong when future teachers work collaboratively with mentor teachers in practicum settings. Collaborative teaching is much needed as future teachers navigate classroom challenges in both online and offline learning. Collaborative teaching is however often seen only as practicum school’s responsibility and not a joint activity with shared goals between university and school that partner to prepare future English language teachers. This paper explores the perspectives of school and university based on the interviews with university supervisors and mentor teachers and related teaching documents. The data were gathered during a six-month practicum implementation in five public schools in Yogyakarta, Indonesia. Guided by Cultural-Historical Activity Theory, a thematic analysis was done to identify points of differences and similarities in the belief and practice of the supervisors and mentor teachers. The results showed that (mis)alignments of the objects, tools, rules, values and roles hamper the goals of the university and school partnership for preparing future teachers. Following CHAT framework, the study recommends that school and university need to align their expectations (object) from practicum activities and set consistent teacher preparation programs (tools, rules) across university and schools.